Book Reviews.
Scientific Management : Frederick Winslow Taylor's Gift to the World? by J.C. Spender and Hugo Kijne. Reviewed by George Hayward
Building a Corporate Internet Strategy : the IT Manager's Guide, by Amit K. Maitra. Reviewed by Gordon Bull.